تحديد شدة ونسبة الإصابة الأعورية (Eimeria tenella) عند الفروج تحت الظروف المناخية لمحافظة اللاذقية (سورية) (Latakia University Journal -Biological Sciences Series, 2016)
أجريت هذه الدراسة لتحديد شدة ونسبة الإصابة الأعورية بالآيميرية تينيلا عند الفروج تحت الظروف المناخية لمحافظة اللاذقية (سورية). تم جمع (1920) عينة أمعاء من مداجن ومحلات ذبح الفروج التجارية إضافة إلى 63 عينة فرشة وزرق تمثل (63) فوجاً لتربية الفروج من مناطق مختلفة من اللاذقية على مدار فترة الدراسة. أظهرت نتائج الفحص التشريحي العياني أن متوسط نسبة الإصابة الأعورية بلغت (51.98%) وقد كانت أعلى نسبة للإصابة الأعورية في فصل الصيف تلاه فصل الخريف ثم فصل الشتاء وأخيراً فصل الربيع  (62.08%) ،(55.42%)، (48.54%)، (41.88%) على التوالي. وتبين أن الإصابة الأعورية المختلطة هي السائدة حيث بلغت (37,45%)، وكانت أعلاها صيفاً (49,17%) و أدناها ربيعاً (28,75%)، في حين بلغت نسبة الإصابة الأعورية المفردة (14,53%)، إذ بلغت أعلاها شتاءً (17,29%) و أدناها صيفاً (12,92%). راوحت شدة أغلب الإصابات الأعورية بين الدرجة الخفيفة (+) والدرجة المعتدلة (++) بنسبة (50%) ، (31,46%) على التوالي. بلغت نسبة الكيسات البيضية للآيميرية تينيلا (48.2%) حيث بلغت أعلاها شتاءً (50,8%) و أدناها ربيعاً (45,2%). This study was conducted to determine the intensity and extensity of caecal Coccidiosis in broiler farms under the climatic conditions of Lattakia. 1920 intestinal samples were collected  from broiler farms and commercial broiler slaughter markets. In addition,  63 litter and fecal samples were collected from different areas in Lattakia. Caecal infection percentage was (51.98%). The highest caecal infection was in summer(62.08%) ,  then  autumn(55.42%),  winter (48,54%), and finally, the least percentage was in spring, (41,88%). It was shown that the percentage of  mixed caecal infection was common that it reached (37,45%).  The highest was in summer (49,17%), while the lowest was in spring (28,75%). Percentage  of single caecal infection reached (14.53%). The highest was in winter (17,29%), while the lowest was in summer (12.92%). Severity of most caecal infection ranged between mild (+) and moderate (++) recording (50%) and  (31,46%) respectively. Oocysts rate of E.tenella reached (48,2%).  the highest was in winter (50,8%), while the lowest was  in spring (45,2%).